Stylistic Analysis of Charles Lamb’s Essay Dream Children: Application of Transitivity Model - Dr. Tariq Mahmood (University of Chitral Journal of Linguistics and Literature, 2021)
This paper aims at the stylistic analysis of Dream Children; A Reverie, an essay by   Charles Lamb. In this research, the researchers apply transitivity as an ideational function of language. The theory of transitivity consists of verbal processes and participant entities. The processes include material, verbal, relational, mental, behavioral, and existential along with their participant entities. The researchers identify ideational function of language in form oof verbal processes used by Lamb in his essay. Furthermore, how the ideational function of the essay contributes to themes such as loneliness, nostalgia, psychology of children and loss and regret. Apart from these, the researchers quantify the verbal processes used in the essay and then categorized them into verbal, mental, relational, material, existential and behavioral processes.  As result, the study uncovers sematico-grammaticality and language skills used to portray the social experiences and life of Lamb.